DISTRIBUIÇÃO DIAMÉTRICA DE UM FRAGMENTO DE FLORESTA ATLÂNTICA NO MUNICÍPIO DE SANTA MARIA DE JETIBÁ, ES - Imaña-Encinas, José; Conceição, Cláudio de Almeida; Santana, Otacílio Antunes; Imaña, Christian Rainier; Paula, José Elias de (Floresta, 2013)
O objetivo do trabalho foi analisar a distribuição diamétrica de um fragmento de Floresta Atlântica localizado na Reserva Biológica Sítio Palmares, Espírito Santo. Em 2.400 m2, foram medidas todas as árvores e palmeiras com DAP igual ou superior a 5 cm. Foram encontrados 1.364 indivíduos extrapolados para hectare, distribuídos em 70 espécies e 33 famílias. O total da população observada apresentou um DAP médio de 14,82 cm e área basal de 41,12 m2.ha-1. Para o total da população observada, foram formadas 13 classes diamétricas, com intervalo de5 cm entre as classes. O ajuste da equação de Meyer mostrou para essa população a tendência da curva do J-invertido. As três primeiras classes diamétricas, de5 a20 cm, concentraram 79% da densidade populacional. Oito espécies apresentaram uma densidade populacional com mais de 40 indivíduos por hectare. Esses indivíduos ficaram concentrados até a classe diamétrica de 40 cm. A análise estatística mostrou que as curvas de tendências da distribuição diamétrica dessas espécies ficaram distribuídas entre a normal, a exponencial negativa e a bimodal. Abstract Diameter distribution of an Atlantic Forest fragment at Santa Maria de Jetibá county, ES. This research aims to analyse the diametric distribution of an Atlantic Forest fragment at Reserva Biológica Sítio Palmares, state of Espírito Santo. In 2,400 m2 all trees and palms with DBH over 5 cm were measured. It identified 1364 individuals distributed into 70 species and 33 families. The community population had a DBH average of 14.82 cm and a basal area of 41.12 m2.ha-1. For the total population, the DBH distribution into 5 cm intervals formed 13 classes. The adjusted Meyer’s equation reveals for this population a tendency to a J-inverse curve. The first three diameter classes from 5 to20 cm concentrated 79% of the total population. Eight species had a population density with more than 40 trees per hectare. These trees were concentrated until the 40 cm distribution classes. The statistical analysis of the distributions curves reveals that these populations were distributed between the normal, j-inverse and bi-modal curves. Keywords: Floristic survey; diametric classes; forest mensuration.